Influence and Persuasion (HBR Emotional Intelligence Series). - Review, Harvard Business (La Vergne : Harvard Business Review Press, 2017)
Changing hearts is an important part of changing minds. With research into how appeals to human emotion can help you make your case and earn authority as a leader, this book presents both comprehensive frameworks for developing a influence and small, simple tactics that you can use to convince others every day.--
Understand the four components of influence: where emotions fit in / Nick Morgan -- Harnessing the science of persuasion: back to behavioral basics / Robert Cialdini -- Three things managers should be doing every day: build trust, a team, and a network / Annie McKee -- Learning charisma: captivate and motivate / John Antonakis, Marika Fenley, and Sue Liechti -- To win people over, speak to their wants and needs: know -- and empathize with -- your audience / Nancy Duarte -- Storytelling that moves people: unite an idea with an emotion, an interview with Robert McKee / by Bronwyn Fryer -- The surprising persuasiveness of a sticky note: build personal connections / Kevin Hogan -- When to sell with facts and figures and when to appeal to emotions: head versus heart / Michael D. Harris.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Influence (Psychology); Persuasion (Psychology); Work -- Psychological aspects; SOCIAL SCIENCE -- General; Influence (Psychology); Persuasion (Psychology); Work -- Psychological aspects; elektronické knihy; electronic books